Effectiveness of MZ2000 Mycorrhizal Biofertilizer on The Growth of Sengon Seedlings - Fahrizal Hazra; Rifqi Puja Novtiar (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2020)
Mycorrhizal biofertilizers contain fungi that are capable of entering and symbiotic mutualism into plant roots and increasing the ability of plants to absorb nutrients. Fertilizer effectiveness testing is needed to protect consumers from the adverse effects of using biofertilizers. This study aims to determine the effectiveness of MZ2000 mycorrhizal biofertilizers and to know mycorrhizal root infections in sengon seedlings in nurseries. The combination treatment of 30 g MZ2000 mycorrhizal biofertilizer with 5 g NPK fertilizer gave the best sengon growth results although it was not significantly different in several parameters compared to the combination treatment of MZ2000 fertilizer dosage and other NPK fertilizers, with the value of agronomic relativity (Relative Agronomic Effectiveness / RAE) 580.80% for high growth and 288.72% for growth in stem diameter and incremental benefit cost ratio (IBCR) analysis of farming by 2.48. So that the dosage of the combination treatment of mycorrhizal biofertilizers and NPK fertilizer is most agronomically and economically effective. With the effectiveness of the fertilizer, the MZ2000 mycorrhizal biofertilizer can be declared to have passed the field effectiveness test.